Antidiabetic activity of Coccinia grandis (L.) Voigt: Bioactive constituents, mechanisms of action, and synergistic effects - I Made Wisnu Adhi Putra&, Nanang Fakhrudin, Arief Nurrochmad, Subagus Wahyuono (Journal of Applied Pharmaceutical Science, 2021)
Diabetes mellitus is a disease caused by irregular carbohydrate metabolism in association with an inadequate insulin level and insulin resistance. As synthetic drugs generate undesired side effects, the treatment of diabetes using natural medicines, especially medicinal plants, has become a potential alternative therapy. Medicinal plants contain many secondary metabolites and play a crucial role in diabetes mellitus therapy. For many years, Coccinia grandis L. Voigt (family: Cucurbitaceae) has been widely utilized, especially in India and Sri Lanka, as a traditional remedy. All parts of this medicinal plant have promising antidiabetic activity with possible mechanisms of action, i.e., regeneration of β-cells in the pancreas, stimulation of insulin secretion, restoration of antioxidant enzymes, enhancement of glucose uptake, regulation of metabolic enzymes, amelioration of the lipid profile, and inhibition of digestive enzymes. The combination of this plant extract with other plants also results in a synergistic effect that enhances its antidiabetic efficacy and reduces the side effects. In this review paper, we present recent findings regarding the antidiabetic activity of C. grandis both in vitro and in vivo, along with its mechanisms of action. We also discuss the synergistic effect of the combination of C. grandis with other plants in order to enhance the antidiabetic potency. Related articles published from 1988 to 2020 in the databases PubMed and Google Scholar were used in this narrative review. This article provides a scientific basis for the antidiabetic activity of C. grandis.
Keywords: Medicinal plant, ivy gourd, diabetes mellitus, synergism